Complementary Alternative Medicine: Kombinasi Terapi Bekam dan Murotal Alquran pada Perubahan Tekanan Darah, Glukosa, Asam Urat dan Kolesterol - Lilin Rosyanti; Indriono Hadi; Askrening Askrening; Maman Indrayana (Poltekkes Kemenkes Kendari, 2020)
Wet cupping (alhijamah) is a therapeutic approach that can cure ailments and promote well-being. The purpose of this study was to determine the effect of cupping therapy while listening to the Qoran on changes in blood pressure, cholesterol, glucose and uric acid. The design used was pre-experimental with One Group Pretest-Posttest design. This research took place at As-syifa Cupping Clinic, Kendari City. The number of research samples is 30 samples of healthy male and female subjects aged 30-60 years. Blood pressure before cupping therapy averaged 10 ± 13.4 after 1 week of therapy, being 4.33 ± 10.72. Then the cholesterol level before therapy was 1.53 ± 507 after 1 week of therapy was 1.03 ± 18, the glucose level before therapy was 2.30 ± 535, after therapy was 2.00 ± 263, the uric acid level before therapy was 1.63 ± 556 after therapy. 1.03 ± 182. The results of statistical tests on blood pressure, cholesterol, glucose and uric acid with the paired sample t-test p = 0.000. Cupping therapy while listening to the qoran can reduce blood pressure, cholesterol levels, blood glucose levels and uric acid levels, so it becomes a recommendation for maintaining health.